Phenotypic plasticity of the planthopper Delphacodes kuscheli (Hemiptera: Delphacidae) revealed by its selectivity, feeding rate and demographic traits on different food quality sites of wheat plants - Brentassi, Maria Eugenia (2014)
Delphacodes kuscheli, a phloem sap-sucking planthopper and the main vector of the Mal de Río Cuarto virus (MRCV) of maize in Argentina, was used to analyze phenotypic plasticity in behavior and demographic traits in response to different food quality, without masking the effects of density dependence and within-plant heterogeneity. We evaluated selectivity of nymphs and adults for different sites of wheat plants and, on sites suspected to have different food quality because of the presence/absence of meristems and therefore different nitrogen content, we evaluated pre-imaginal survival, nymphal developmental time, proportion of macropterous morphs, adult longevity and feeding rate. Delphacodes kuscheli showed a positive selection for plant zones suspected to have higher food quality and on them insects developed faster, exhibited higher nymphal survival and adult longevity and produced a lower proportion of macropterous morphs. Also on sites suspected to have lower food quality the number of honeydew droplets excreted per day increased and the mean diameter diminished, suggesting that the planthopper could probe more frequently to compensate for different food quality.